Effect of SARS-COV-2 on kidney tissue: a narrative review - Flores Gavino, Aldo (2021)
We describe evidence on SARS-CoV-2 effect on the kidney. We carried a narrative review of articles published in SCOPUS and PUBMED until September 2020. The results were divided into six topics: evidence of direct effect of virus on the kidney, mechanisms of cellular invasion, mechanisms of kidney injury, and potential therapeutic implications.  SARS-Cov-2 gains access to proximal tubule cells and podocytes via ACE-2 receptors. Viral invasion and replication may induce kidney damage through a direct cytopathic effect and immune-mediated damage. Due to ACE-2 cellular expression, Renin–Angiotensin–Aldosterone System Inhibitors have been proposed as potential treatment for COVID-19. However, current evidence does not support its therapeutic use.